2010
DOI: 10.2139/ssrn.1740371
|View full text |Cite
|
Sign up to set email alerts
|

Sorting and the Output Loss Due to Search Frictions

Abstract: We analyze a general search model with on-the-job search and sorting of heterogeneous workers into heterogeneous jobs. This model yields a simple relationship between (i) the unemployment rate, (ii) the value of non-market time, and (iii) the max-mean wage di¤erential. The latter measure of wage dispersion is more robust than measures based on the reservation wage, due to the long left tail of the wage distribution. We estimate this wage di¤erential using data on match quality and allow for measurement error. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…Unfortunately, the literature has recently established that the key identifying assumptions of this regression approach are inconsistent with the standard equilibrium sorting models and that the worker and firm fixed effects identified using this methodology have no economic interpretation in the context of these models. 1 The key problem is that the assumption underlying the fixed effect regression is 1 Gautier and Teulings (2006) were the first to establish this in a model of sorting based on comparative advantage. This important class of models violates the underlying assumption of the fixed effect regression that workers and firms are globally rankable.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the literature has recently established that the key identifying assumptions of this regression approach are inconsistent with the standard equilibrium sorting models and that the worker and firm fixed effects identified using this methodology have no economic interpretation in the context of these models. 1 The key problem is that the assumption underlying the fixed effect regression is 1 Gautier and Teulings (2006) were the first to establish this in a model of sorting based on comparative advantage. This important class of models violates the underlying assumption of the fixed effect regression that workers and firms are globally rankable.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, this assumption is only relevant for identifying rankings of workers and firms when they can be ranked. In Hagedorn, Law, and Manovskii (2014), we showed that if some agents cannot be ranked, for example, firms in the comparative advantage model of Gautier and Teulings (2012), our identification strategy will reveal this and it will continue to recover the production function correctly.…”
Section: Basicsmentioning
confidence: 91%
“…In the presence of frictions, let E fric be the expectation of f : 23 An alternative approach to measuring the cost of mismatch was pursued by Eeckhout and Kircher (2011). They noted (as did Teulings and Gautier (2004) and Gautier and Teulings (2006)) that differentiating the wage equation (such as (A.2) in the Supplemental Material), the cross-partial derivative of the wage equals the cross-partial derivative of the production function multiplied by the worker bargaining weight. They also showed that in their two-period model, where a period with search frictions is followed by a frictionless period and there is no discounting, and under the assumption that the production function globally induces PAM or NAM, the average cross-partial of the production function can be theoretically related to the output cost of mismatch.…”
Section: Measuring the Effect Of Search Frictions On Outputmentioning
confidence: 97%
See 1 more Smart Citation
“…Eckstein and Van den Berg (2007) provided an insightful survey of this literature. One key difference between the current paper and previous research is that this paper seeks to understand how search frictions affect the level of asset prices and of asset allocations (and the role of intermediaries), while most papers that structurally estimate labor-market search models focus on how search frictions affect wage dispersion across workers (notable exceptions are Gautier andTeulings (2006, 2015). Search models have also been applied to housing markets, with Carrillo (2012) being the closest empirical paper.…”
Section: Related Literaturementioning
confidence: 99%